GENERALIZATION OF ESTIMATION RESULTS OF THE SHEEP ORGANISM ADAPTIVE SYSTEM - Ладиш, І. О.; Бублик, В. М.; Знагован, С. Ю. (Scientific Progress & Innovations, 2013)
As to the results of morphological and biochemical research of blood the clinical and biological coefficient with lymphocytic-neutrophilic index in its basis was developed. In neonate sheep of the precos breed, there was a higher coefficient in comparison with lambs from Luhansk region as a consequence of higher level in adaptation mechanisms in organism of the newborn lambs of the breed. It was stated that sheep of Askania merinos breed which are bred under the conditions of the Kherson region have been more adapted to the physiological and technological stresses.